THE DEVELOPMENT AND IMPLEMENTATION OF MERDEKA CURRICULUM IN 21 CENTURY - Zulhadi Zulhadi; Absharini Kardena; Arino Susanto (International Journal of Teaching and Learning, 2025)
This study aims to collect information about the steps of curriculum development based on Kerangka Kualifikasi Nasional Indonesia (KKNI) and Kurikulum Merdeka. On the other side, this study examines the similarities and compatibility between these two development approaches with the principles of Educational Technology and the implementation of the Kurikulum Merdeka in 21st-century learning. The methodology used in this research is qualitative descriptive, which will present data in descriptive statements. Data were obtained from literature review of previous studies and government policies. The results of this study indicate the need for steps to accelerate the development of the Kurikulum Merdeka implemented in educational institutions where teachers can play a role as learning leaders capable of utilizing the Merdeka Mengajar Platform and prioritizing project based learning. Based on the literature review and research findings, it can be concluded that there is continuity between the KKNI curriculum and the Kurikulum Merdeka, and there are similarities and compatibility in accordance with the principles of Educational Technology. Therefore, in the implementation of the Merdeka Curriculum, all of these are essentially oriented towards improving the competencies of students and all supporting systems that aim to achieve high- quality graduates.